Applicability of evaluation indices for asphalt and filler interaction ability. (1st September 2017) - Liu, Guoqiang; Zhao, Yongli; Zhou, Jian; Li, Jing; Yang, Tao; Zhang, Jiupeng
Highlights: △G ∗, K-B-G ∗, L-A-δ and K-B-δ are used to study the asphalt and filler interaction. The asphalt-filler interaction ability increases with temperature increasing and decreases with loading frequency increasing. The K-B-δ has the most significant sensitivity followed by L-A-δ, △G ∗ and K-B-G ∗ sequentially. Abstract: The asphalt and filler interaction plays a significant role on the performances of asphalt mixtures, and the asphalt and filler interaction ability can be evaluated by the rheological properties. In this paper, one kind of matrix asphalt binder and three kinds of fillers were selected to prepare asphalt mastics with different filler volume fractions respectively, and the dynamic shear rheological properties of asphalt mastics were measured to analyze the four evaluation indices of △G ∗, K-B-G ∗, L-A-δ and K-B-δ . Results indicate that △G ∗ and K-B-G ∗ cannot represent the effects of temperature on asphalt and filler interaction ability. However, the two indices can reflect the effects of loading frequency on asphalt and filler interaction ability. L-A-δ and K-B-δ not only represent the effects of temperature on asphalt and filler interaction ability but also the effects of loading frequency on asphalt and filler interaction ability. The higher temperature is, the stronger asphalt and filler interaction ability is. But the higher loading frequency is, the worse asphalt and filler interaction ability is. And then the sensitivity analysis of evaluation indices was also conducted, and finding that the sensitivity from high to low is (1) K-B-δ, (2) L-A-δ, (3) △G ∗, and (4) K-B-G ∗ .